The Influence of Spirituality, Colleagues and Organizational Culture on Job Satisfaction of Madrasah Diniyah Teachers - Mohammad Ma’ruf Rois; Sumartik (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of Spirituality, Colleagues, and Organizational Culture on Teacher Job Satisfaction at Madrasah Diniyah Salafiyah Ar-Riyadl, Jabon District. This research is included in the type of quantitative research with hypothesis testing. The sample used in this study were 50 respondents. The sampling technique used was non-probability sampling technique. The analytical tool used in this research is a path analysis technique with the help of software for the operating system called Smart-PLS (Partial Least Square) Version 3.0. The data used in this research are questionnaire data and data sourced from Madrasah Diniyah Salafiah Ar-Riyadl, Jabon District. Data collection techniques using questionnaires. The results of this study prove that Hypothesis 1: spirituality variable has no effect on job satisfaction. Hypothesis 2: coworkers affect job satisfaction. Hypothesis 3: organizational culture has an effect on job satisfaction.